2015
DOI: 10.3390/nu7115472
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns during Pregnancy Are Associated with Risk of Gestational Diabetes Mellitus

Abstract: Maternal dietary patterns before and during pregnancy play important roles in the development of gestational diabetes mellitus (GDM). We aimed to identify dietary patterns during pregnancy that are associated with GDM risk in pregnant U.S. women. From a 24 h dietary recall of 253 pregnant women (16–41 years) included in the National Health and Nutrition Examination Survey (NHANES) 2003–2012, food items were aggregated into 28 food groups based on Food Patterns Equivalents Database. Three dietary patterns were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
135
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(144 citation statements)
references
References 38 publications
4
135
1
4
Order By: Relevance
“…22,44 Although we did not find a significant association between tertiles of uPDI and GDM in the present study, elevated risk of GDM has been reported in other studies. 6,20,43 It is possible that this is because of lowest tertile of uPDI still having average fasting blood glucose above the cut-off for GDM, making it challenging to look at differences in GDM outcomes. Although the exact mechanism through which plant-based diets might affect GDM is not well understood, several suggestions have been made.…”
Section: (B)mentioning
confidence: 99%
See 2 more Smart Citations
“…22,44 Although we did not find a significant association between tertiles of uPDI and GDM in the present study, elevated risk of GDM has been reported in other studies. 6,20,43 It is possible that this is because of lowest tertile of uPDI still having average fasting blood glucose above the cut-off for GDM, making it challenging to look at differences in GDM outcomes. Although the exact mechanism through which plant-based diets might affect GDM is not well understood, several suggestions have been made.…”
Section: (B)mentioning
confidence: 99%
“…The prevalence of GDM has increased steadily, with 14% of pregnancies in USA, 5.7% of pregnancies in Australia, and 5–10% of pregnancies in Asian countries presenting with GDM. In Iran, the prevalence of GDM has been estimated at 3.4% of all annual pregnancies . GDM is considered as a significant risk factor for several other comorbidities in both mothers and their newborns …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Эти данные находят подтвержде-ние в ряде работ иностранных авторов [13,14]. Напри-мер, в исследовании здоровья медицинских сестер тип питания, характеризующийся наименьшим уровнем потребления фруктов и овощей, был ассоциирован с по-вышением риска развития ГСД по сравнению с женщи-нами с наибольшим уровнем потребления [15].…”
Section: обсуждение основного результата исследованияunclassified
“…Regular physical activity (PA), adequate gestational weight gain (GWG) and healthy eating may lower the incidence and severity of serious conditions associated with pregnancy, including, gestational diabetes mellitus [1][2][3], pregnancy-induced hypertension [2], macrosomia [1] and small for gestational age infants [4]. In addition, daily exercise for the pelvic floor muscles may prevent and treat urinary incontinence [5].…”
Section: Introductionmentioning
confidence: 99%